Weather conditions at Vernadsky Station in 2011 and expected temperature regime in the summer of 2011-2012 on the basis of instrumental observations of 2011 - V. F. Martazinova; V. E. Tymofeyev; E. K. Ivanova (Ukrainian Antarctic Journal, 2012)
The description of weather patterns in 2011 compared to the standard climatic norm and contemporary conditions. The 2011 winter has been colder than previous winters during 1996-2010, and characterized by strong oscillations in daily temperature range. A more detailed description of individual periods with settled weather in January, colder weather in April, significant precipitation in February, May and October, as well as conditions in the atmospheric circulation are described. Expected state of the temperature regime in the summer of 2011 2012 is estimated: beginning of the summer season at Academic Vernadsky is projected as a relatively cool.  The results of the comparison of data of Troposphere Mobile Meteorological Measuring Complex installed in the 2011 season show some systematic errors which can be taken into account when making climate and operational reports. Introduction of the new Meteorological station allowed maintaining regular performance of standard synoptic routine and data transfer to World Data Center, as well as near-real time records of weather according to WMO and the National Hydrometeorological Service requirements.